VALIDATION OF KPG INDEX “CLASSIFICATION METHOD TO PREDICT ORTHODONTIC TREATMENT DIFFICULTY LEVEL OF IMPACTED CANINES” - Iftikhar, Ayesha; Jahanzeb, Tayyaba (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the position of impacted canine in 3 dimensions and estimate the difficulty of treatment using 3D “KPG index”, a new classification method. Study Design: Cross sectional analytical study. Place and Duration of Study: Orthodontic Department, Rehman College of Dentistry, Peshawar, from Aug to Oct 2020. Methodology: 3D cone beam computed tomography (CBCT) scans of 43 subjects with 47 impacted canines were obtained. Using KPG index, 6 measurements were taken for each impacted tooth in three planes. The scores were later summed up. Based on the cumulative scores, each impaction was classified into the difficulty categories of Easy (0–7), Moderate (8–14), Difficult (15–19), and Extremely Difficult (20+). Comparison of Gender and position of impacted canine with the KPG treatment difficulty index was also performed. Results: Impacted canines were found to be on the left and palatal side with a female predilection. Canines scored with KPG index were mostly in the moderate category. Highest percentage of the impacted canines were in Sector II, followed by sector III and IV. Comparing KPG treatment difficulty index of impacted maxillary canines found on the right and left sides (p=0.087), buccal or palatal (p=0.545), males and females (p=0.279), in-statistically significant difference was found. Conclusion: 3D imaging has allowed us to precisely locate the impacted canine in 3 sagittal, coronal and axial planes. Hence, KPG index dictated our anticipated difficulty of treatment.